The Covid 19 Pandemic as a Strain in Increasing Domestic Violence (An Overview of Restorative Justice in Sustainable Crime) - Ni Nyoman Juwita Arsawati; I Made Wirya Darma; Ni Gusti Agung Mas Triwulandari; Dewi Bunga (Fakultas Hukum Universitas Muhammadiyah Magelang, 2022)
The COVID-19 pandemic has become a global pandemic that has changed the order of human life in almost all parts of the world. Indonesia is also one of the countries affected by the Covid-19 pandemic. The Indonesian government has established public policies to prevent the spread of the COVID-19 virus, one of which is the policy on limiting community activities by diverting work to be done from home (Work from Home). The pandemic condition has an impact on increasing cases of domestic violence. Various factors can cause domestic violence during the pandemic, the main one is the economic factor. This study aims discusses the Covid-19 pandemic as a